Interaction between plants and epiphytic lactic acid bacteria that affect plant silage fermentation - Chen, Lijuan; Wang, Yili; Li, Xi; MacAdam, Jennifer W.; Zhang, Yunhua (Frontiers in Microbiology, 2023)
Lactic acid bacteria (LAB) have the ability to ferment water-soluble carbohydrates, resulting in the production of significant amounts of lactic acid. When utilized as additives in silage fermentation and feed, they have been shown to enhance the quality of these products. Epiphytic LAB of plants play a major role in the fermentation of silage plants. Plant species in turn affect the community structure of epiphytic LAB. In recent years, an increasing number of studies have suggested that epiphytic LAB are more effective than exogenous LAB when applied to silage. Inoculating silage plants with epiphytic LAB has attracted extensive attention because of the potential to improve the fermentation quality of silages. This review discusses the interaction of epiphytic LAB with plants during silage fermentation and compares the effects of exogenous and epiphytic LAB on plant fermentation. Overall, this review provides insight into the potential benefits of using epiphytic LAB as an inoculant and proposes a theoretical basis for improving silage quality.